The United States to the rescue: Financial assistance to Mexico in 1982 and 1995 - Nora Lustig (CEPAL Review, 1997)
This article analyses the financial rescue measures taken by the United States in the Mexican payments crises of August 1982 and January 1995. On both occasions, Mexico was on the brink of suspending payments on its external debt, and both times this was avoided thanks to rescue measures. The implications of the two financial rescue programmes were very different, however. The measures taken in August 1982 were followed by a period of many years in which Mexico was practically excluded from private loan markets. In contrast, the 1995 rescue programme was quickly followed by renewed access by Mexico to private capital markets.